Steroid resistance in asthma: mechanisms and potential therapies - Adcock, Ian (Henry Stewart Talks, 2011)
Overview of asthma pathophysiology, Patterns of severe refractory asthma, Methods to improve steroid efficacy in severe asthma, Mechanisms that induce steroid insensitivity; Th2 cytokines, IL-17 and infections, Pathophysiology of severe treatment refractory asthma, Novel anti-inflammatory approaches, Can new combinations of drugs reverse steroid insensitivity in severe asthma?
Archived at 2022/01/31